Physics education students’ science process skills - Darmaji Darmaji; Dwi Agus Kurniawan; Irdianti Irdianti (International Journal of Evaluation and Research in Education (IJERE), 2019)
The purpose of this study was to determine the description of the process carried out in the physics education study program on the lens material. The process skills used in this study are the methods used, namely measurement, measurement and measurement processes which consist of table data, data, and training, conducting experiments. Total sampling technique was choosen to recruit 91 students to participate in the study. They are contracted in basic physics practicum courses. The results show that physics students have done their own lab work in the learning process that has been incorporated into the good category. The science process skills that are most mastered in concave movement practices are observations with a percentage of 51.65% and have an average of 82.76. Whereas for convex lens practices are skills and data that have good categories with a percentage of 81.32% and have an average of 73.67.